Populações de plantas de milho e de feijão, no sistema de cultura consorciada, utilizadas na zona da mata de Minas Gerais - Vieira , Clibas; Aidar , Homero; Faria Vieira , Rogério (Revista Ceres, 2025)
In a recent survey in the Zona da Mata, state of Minas Gerais, it was found that most commercial fields had a population of 20 to 47 thousand maize plants per hectare associated with 12 to 75 thousand bean plants in the "rainy" season (first bean planting) and 120 to 400 thousand bean plants in the "dry" season (second bean planting).